Apple motion 5 cookbook : over 110 recipes to build simple and complex motion graphics in the blink of an eye - Harauz, Nick (Packt Pub., 2013)
Step-by-step, practical recipes to build simple and complex Motion Graphics with Motion 5""Apple Motion 5 Cookbook"" is designed for Final Cut Pro X video editors and Motion 5 users looking to gain more knowledge of how Motion works, and to get more of a 'WOW' factor in projects. It's also aimed at designers and motion designers alike, who are looking to build on their skillsets.- Resumé vydavatel
"Quick answers to common problems"--Cover.
Includes index.
Keywords: počítačová animace; počítačová grafika; computer animation; computer graphics; elektronické knihy; příručky; electronic books; handbooks and manuals